Peningkatan Keterampilan Sosial Melalui Model Cooperative Learning Berbasis Kecerdasan Interpersonal pada Pembelajaran IPS Kelas IV di Era New normal - Roid Ismail Ardho; Atto' Maulana (Universitas Muhammadiyah Magelang, 2022)
This study aims to test the Cooperative Learning model based on interpersonal intelligence in social studies subjects is able to improve the social skills of fourth grade elementary school students. The research design used was CAR using 3 cycles with 6 meetings. The research subjects in this study were 32 students, who had low social skills. The variables in the study consisted of 3 variables, namely input variables: Fourth grade students have low social skills, process variables: the use of Interpersonal Intelligence-based Cooperative Learning Learning Models in Social Studies Subjects Class IV, output variables: improve students' social skills in the new normal era. The data collection in this research is in the form of observations that reveal data about the development of social skills in Cooperative Learning activities based on interpersonal intelligence. The results showed that the social skills of SD Muhammadiyah 1 Alternatif Kota Magelang students increased. Before the action was taken, most of the students had low and moderate social skills. However, in Cycle III, it can be seen that there was an increase in students' social skills, namely (6.3%) having good category social skills and (93.3%) having very good social skills category. The conclusion is that the social skills of fourth grade students at SD Muhammadiyah 1 Alternatif Kota Magelang can be improved when children are invited to apply learning using a Cooperative Learning model based on interpersonal intelligence.